Mustafa Kemal Paşa'nın başkomutanlığa getirilmesi - (:unkn) unknown (My University, 2014)
Mustafa Kemal Paşa, Milli Mücadele döneminde Kütahya ve Eskişehir Muharebelerinden sonra TBMMnin 5 Ağustos 1921 tarihli kanunuyla ve üç ay süreyle Türk Ordusunun Başkomutanlığına getirilmiştir. 20 Tem- muz 1922de Başkomutanlık yetkisi TBMM tarafından süresiz uzatılan Mustafa Kemal Paşa, Büyük Taarruzda ordunun başına geçerek zaferin kazanılmasında önemli bir görev üstlenmiştir.

In the era of National Struggle, after the battles of Kutahya and Eski- sehir, Mustafa Kemal Pasha had been appointed to chief in command of Turkish army for 3 months time with jurisdiction of TBMM legislation in August 5th, 1921. With his chief in command jurisdiction being extended without time limit by TBMM in July 20th, 1922, Mustafa Kemal Pasha had taken the helm of Turkish army in The Great Offensive Dumlupınar Battle and played a very important role in victory.
Calling the duty of Mustafa Kemal Pasha to chief commander
Keywords: Tarih